Access to N−CF3 Formamides by Reduction of N−CF3 Carbamoyl Fluorides. (23rd November 2022) - Zivkovic, Filip G.; D.‐T. Nielsen, Christian; Schoenebeck, Franziska
Abstract: The departure into unknown chemical space is essential for the discovery of new properties and function. We herein report the first synthetic access to N ‐trifluoromethylated formamides. The method involves the reduction of bench‐stable N CF3 carbamoyl fluorides and is characterized by operational simplicity and mildness, tolerating a broad range of functional groups as well as stereocenters. The newly made N −CF3 formamide motif proved to be highly robust and compatible with diverse chemical transformations, underscoring its potential as building block in complex functional molecules. Abstract : The first synthetic access to N ‐trifluoromethylated formamides is reported. The method involves the reduction of bench‐stable N −CF3 carbamoyl fluorides. In contrast to e.g. N −Me formamides, the newly made N −CF3 formamides do not show rotamers at room temperature. Moreover, they are highly robust and compatible with diverse chemical transformations.